Plant growth-promoting rhizobacteria on peanut seedlings (Arachis hypogaea L.): Isolation, taxonomical, and functional characterization - Ezequiel Darío Bigatton; Ibrahim Ayoub; María Ángeles Castillejo; Carolina Merlo; Carolina Vázquez; Mariela Valeria Archilla; Marina Bruno; María Paula Martín; Romina Paola Pizzolitto; Lucas Esteban Dubini; Enrique Iván Lucini; Ricardo Javier Haro (Oil Crop Science)
To improve crop yields, global food production needs sustainable agronomic tools like Plant Growth-Promoting Rhizobacteria (PGPR). Region-adapted PGPR strains are crucial to increasing peanut production. Argentina is the seventh-largest peanut producer, and Córdoba is the main region with 250,000 ​ha (75% of the total sowing area). This study aimed to isolate, identify, and characterize the biocontrol and growth promotion capacity of PGPR strains belonging to the Bacillus and Pseudomonas genera. The strains were tested against Sclerotinia minor, Sclerotium rolfsii, Fusarium verticillioides, and Aspergillus flavus for biocontrol assays. For growth promotion, pot trials used two peanut cultivars, ASEM 400 INTA and Granoleico, under 40% and 60% field capacity under two water regimes. The isolated strains were Bacillus velezensis, B. subtilis, B. tequilensis, B. safensis, B. altitudinis, and Pseudomonas psychrophila. These strains demonstrated in-vitro phosphorus solubilization, nitrogen fixation, ammonification, nitrification, enzyme releasing, phytohormones production, and high biocontrol capacity of over 75%. SC6 and RI3 (both B. velezensis) and P10 (P. psychrophila) exhibited outstanding performance. They significantly promoted peanut root biomass by more than 50% and leaf area by 30%, with increased chlorophyll content index and leaf relative water content, particularly under water stress conditions (40% field capacity). According to the results, RI3, SC6, and P10 could be classified as PGPR, which supports the results obtained in other field studies with these same microorganisms. Future investigations should prioritize the development of industrial formulations to assess their effectiveness in alternative crops and to incorporate them into other agricultural practices.